Karakteristik Fluiditas Pada Variasi Saluran Proses Pengecoran Kuningan Dengan Metode Pengecoran Evaporative - Wirastawan, I Made; Sugita, I Ketut Gede; Priambadi, IGN. (Teknik Desain Mekanika; Vol 11 No 2 (2022): April 2022 : Teknik Desain Mekanika, 2022)
Abstract Brass is an alloy of copper (Cu) and zinc (Zn) and can be used in various forms of crafts such as sculpture. The right casting process is needed so that product defects and lack of fluidity in filling the casting pattern can be overcome so that the desired shape is achieved. The casting method used is the evaporative casting method. In this study, temperatures of 900, 950 and 1000°C were used. The specific gravity of the polystyrene foam used was 0.012, 0.014, 0.016 and 0.018 gr/cm³. fluidity test to determine the flowability of the brass castings that fill the mold. Fluidity increases with increasing pouring temperature. The highest fluidity at a pouring temperature of 1000°C is 150 mm with a density of 0.012 gr/cm3, and the lowest fluidity is at a pouring temperature of 900°C of 13 mm with a density of 0.016 gr/cm3. Characteristics of the relationship between channel variation and flow velocity, the largest flow velocity was at a density of 0.016 gr/cm3, a pouring temperature of 1000°C with a thickness of 5 mm was 26.61 mm/s, while the lowest flow velocity was obtained at a density of 0.012 gr/cm³ with a thickness of 1.5 mm by 2.37 mm/s. Keywords: Fluidity, evaporative casting, polystyrene foam.